A Body in Motion: The Afterlives of the Tomb of Henry Howard, Earl of Northampton - Ford, Lisa (Material Culture Review, 2012)
The impressive monument erected to Henry Howard, Earl of Northampton in the church of St. Mary de Castro in Dover Castle ca. 1614-1616 epitomized his success in reviving the Howard family name and fortune. But neglect and accident not only reduced his proud statement to a lesser form, but also necessitated its move from its original site to Trinity Hospital in Greenwich. This essay examines the incidents that prompted the moving and later reworking of the monument, which provide an interesting case study of the effects of time and circumstance upon a seemingly stable object.